Lower cognitive performance in 81-year-old men with greater nocturnal blood pressure dipping - Axelsson, Johan (Dove Medical Press, 2009)
Abnormal day-to-night blood pressure (BP) pattern have been found to be associated with cerebrovascular damage, yet studies of the elderly 80 years of age and above, for whom the risk pattern may be different due to ageing and age-associated diseases, are lacking. Ninety-seven 81-year-old men underwent ambulatory BP monitoring and were given six cognitive tests, 79 of the men completing the cognitive test battery. The odds ratio (OR) for performing one standard deviation below the mean on any cognitive test was calculated using a forward stepwise logistic regression model, confounding factors being controlled for. Groups defined in terms of day-to-night changes in BP were compared in this respect. Cognitive performance was lower (OR 3.6; P = 0.017) in the group usually described as dippers (10%–20% nocturnal drop in systolic BP [SBP]) as compared with nondippers (<10% drop). The tertile with the greatest SBP fall (10.6%–19.8%, a range considered as normal among middle aged) showed lowest cognitive performance (OR 4.7; P = 0.008) as compared with the middle tertile (5.1%–10.5% drop). The mean nocturnal fall in SBP was 7.4%, significantly greater in those with lower rather than higher cognitive performance. A nocturnal drop in SBP of ≥10% was associated with lower cognitive performance in these elderly men. The limits to normal dipping appear to be shifted in the direction of a lesser drop in the very elderly.